2021
DOI: 10.3390/ijms22094760
|View full text |Cite
|
Sign up to set email alerts
|

SRC-3, a Steroid Receptor Coactivator: Implication in Cancer

Abstract: Steroid receptor coactivator-3 (SRC-3), also known as amplified in breast cancer 1 (AIB1), is a member of the SRC family. SRC-3 regulates not only the transcriptional activity of nuclear receptors but also many other transcription factors. Besides the essential role of SRC-3 in physiological functions, it also acts as an oncogene to promote multiple aspects of cancer. This review updates the important progress of SRC-3 in carcinogenesis and summarizes its mode of action, which provides clues for cancer therapy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 171 publications
0
15
0
Order By: Relevance
“…Interestingly, analysis of separate publically available RNA-seq dataset (GEO accession: GSE65099) ( 45 ) showed that SRC-3 RNA levels are significantly increased in the endometrium of patients diagnosed with RPL ( Figure 2F ), suggesting that perturbation of the homeostatic levels of SRC-3 may be linked to this endometrial pathology. It's important to note that dysregulation of SRC-3 expression is known as a critical causal factor in the genesis and progression of numerous tissue pathologies, including tumorigenesis and metastasis ( 14 , 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, analysis of separate publically available RNA-seq dataset (GEO accession: GSE65099) ( 45 ) showed that SRC-3 RNA levels are significantly increased in the endometrium of patients diagnosed with RPL ( Figure 2F ), suggesting that perturbation of the homeostatic levels of SRC-3 may be linked to this endometrial pathology. It's important to note that dysregulation of SRC-3 expression is known as a critical causal factor in the genesis and progression of numerous tissue pathologies, including tumorigenesis and metastasis ( 14 , 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…EGFR is increasingly considered a biomarker of tumor drug resistance, and its amplification or secondary mutation occurs under the pressure of drugs ( Jang et al, 2020 ). SRC, a proto-oncogene complex protein kinase, promotes the development of cancer in many respects ( Li L. et al, 2021 ). SRC kinase plays an important role in promoting tumor growth and progression, and its activity is related to the low survival rate of patients ( Dasgupta et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous ndings has revealed that the histone methyltransferase NSD2 protects SRC-3 from degradation through forming liquid-liquid phase separation and renders resistance to PIs. 19 SRC-3 promotes numerous aspects of cancer, such as initiation, progression, and chemoresistance 25 , and suppression of SRC-3 levels and/or activity are e cient enough to alter its transcriptome. 26,27 Several studies have demonstrated that stimuli could induce multiple posttranslational modi cations of SRC-3, including phosphorylation, ubiquitination, SUMOylation, acetylation and methylation 25,28 .…”
Section: Discussionmentioning
confidence: 99%
“…19 SRC-3 promotes numerous aspects of cancer, such as initiation, progression, and chemoresistance 25 , and suppression of SRC-3 levels and/or activity are e cient enough to alter its transcriptome. 26,27 Several studies have demonstrated that stimuli could induce multiple posttranslational modi cations of SRC-3, including phosphorylation, ubiquitination, SUMOylation, acetylation and methylation 25,28 . In this study, we report that hypoxia is a new stimulates for SRC-3 expression without affect its transcription level.…”
Section: Discussionmentioning
confidence: 99%